Design and fabrication of air uplift chamber for testing roof panel systems in the Philippines - Bisa, Harvey O.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Strong typhoons inflict damages to residential houses especially on its building envelope. Building envelope such as roof panel systems are subjected to negative pressures. These negative pressures produced by the strong winds, pull the roofing panels away and the only connection that holds the roofing are its fasteners. In order to have deeper knowledge on the modes of failure and to gather more data for the overall roofing strength, specialized equipment is needed to test different kinds of materials that are locally available in the Philippines. This study deals with the design and fabrication of testing equipment for determination of overall strength of roofing systems. The Air Chamber is made of fully welded steel frames and plates with 2.4 x 2.4 x 0.4m inner dimension. Air Chamber contains a viewing window and two 1.5" Pipes as inlet or outlet for air. Negative pressure is induced by a Centrifugal Ring Blower operating at Single Phase, 220V, 0.75kW with a rated positive and negative pressure of 15kPa. The discharge of the blower is at 2.5 m3/min. In addition to fabrication of the air chamber and connecting it to Centrifugal Ring Blower, roofing assemblies with 75mm Metal Tek-Screw, 0.4 mm thick Roofing (Wave Corrugations) and 50 x 75 x 1.0mm C-Purlins were tested to measure physical deformations and observe splitting after application of uplift pressures. Roofing specimen size is 2.6m x 2.6m with tek-screws spaced at 600mm and purlins spaced at 750mm. Roofing specimens were turned upside down and placed at the top of the chamber and sealed. The chamber was sealed using a combination of Polyethylene sheet layers, foam insulation at air chamber lids and held intact by metal C-clamps and duct tapes. Air Chamber is equipped with three different types of sensors namely BMP 180 Barometric Pressure Sensor, S-Type Full Bridge Load Cell at 200kg Capacity and LVDT (Linear Varying Differential Transformer) with a stroke of 0-50mm. These sensors will measure the suction pressure inside the chamber, force in the middle fastener and the deformation at the middle of the specimen, respectively. The sensors are all powered by Variable / Regulated DC Power Supply and the data acquisition used are Arduino Uno Microcontroller, Arduino IDE 1.8.5 and CoolTerm for Pressure Gauge and LVDT, NI SCXI 1600 Analog to Digital Converter, SCXI 1520 Strain Bridge Module, SCXI 1314 Signal Conditioning Module, NI DAQmx 9.9 and Labview 2010 for the load cell. Sampling frequencies of Pressure Sensor, LVDT and Load Cell are at 50Hz, 500Hz and 1 kHz, respectively. Data acquisition from all the sensors is synchronized during the testing. Three roofing assemblies are tested. The first specimen has two layers overlap of corrugated roofing at the middle fastener. The second specimen has only one layer of roofing at the middle fastener but the overlaps on the specimen have two crests only. And lastly, the third specimen has one layer at the middle fastener but have three crests on the overlaps. The results are Load vs. Displacement Curve and Load vs. Pressure Curve and Load vs. Pressure Curve of the middle fastener and center of the roofing assembly. The Air Chamber can be used to test more building materials especially those that are exposed to high velocity winds or gusts. The air chamber will provide threshold values of the building envelope materials. These threshold values will be used for future researches on CFD simulations of building and risk assessment in the Philippines. It is recommended that the Air Chamber can be further improved by using VFD (Variable Frequency Drive) to control the valve resulting to simulated negative and positive pressures. It is also recommended to make the Air Chamber fully instrumented with LVDT and Washer / Ring Type Load cells to have a deformation profile and load vs. displacement curve for all fasteners of the roofing assembly during the test.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Roofing -- Testing